DAMPAK KREDIT PERBANKAN TERHADAP PENGEMBANGAN UMKM DI KECAMATAN LABUHAN BADAS KABUPATEN SUMBAWA - Nining Sudiyarti; A Asmini; Muhammad Zainuddin Asri (Pusat Riset dan Publikasi, 2025)
This study aims to know the impact of bank credit toward development of micro, small and medium enterprise (UMKM) in Labuhan Badas Sub-District, Sumbawa District. This study used a comparative method to compare sales turnover, quantity of goods, profits, and expenses before and after receiving bank credit. Quantitative data was collected directly from respondents using a questionnaire. The data analysis technique used were descriptive statistical analysis, normality test and the wilcoxon signed rank test. The results of the study showed that bank credit had positive and significant impact toward sales turnover, quantity of goods, profits and expenses before and after receiving UMKM banking credit in Labuhan Badas District, Sumbawa District. The results of statistical analysis that was done with the wilcoxon sign rank test formula showed that all respondents who were became sample had higher sales turnover, profit, expense, and quantity of goods after got credit than sales turnover before got credit. Thus, it can be concluded that there was a positive and significant difference in sales turnover, profit, expenses, and the number of MSMEs between before and after obtaining bank credit. Sales turnover, profit, expenses, and the number of MSMEs after obtaining bank credit are higher than before obtaining bank credit.